2013
DOI: 10.1093/rpd/nct011
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the X-ray system setting on patient dose and image quality; a case study with two interventional cardiology systems

Abstract: This study investigates the influence of the initial X-ray system setting on patient doses and image quality in interventional cardiology procedures. Two dedicated interventional cardiology systems were studied: a system with image intensifier (II) and a flat detector (FD) system. Entrance surface air kerma (ESAK) rates in fluoroscopy and ESAK per frame in the acquisition mode were measured on the surface of a PMMA phantom for the field of views (FOV) of 23 and 17 cm (II system) and 25 and 20 cm (FD system). S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…The advantages of such a protocol would be a reduction in radiation exposure to the personnel involved and (less crucial in horses) the patient. In human medicine, progresses have been made in optimising the use of DR, particularly in the area of reducing radiation dose (Seibert 2008, Uffmann and Schaefer‐Prokop 2009, Sun and others 2012, Vassileva and others 2013). There has been a move away from the principle of ‘image quality as good as possible’ to ‘image quality as good as needed’.…”
Section: Discussionmentioning
confidence: 99%
“…The advantages of such a protocol would be a reduction in radiation exposure to the personnel involved and (less crucial in horses) the patient. In human medicine, progresses have been made in optimising the use of DR, particularly in the area of reducing radiation dose (Seibert 2008, Uffmann and Schaefer‐Prokop 2009, Sun and others 2012, Vassileva and others 2013). There has been a move away from the principle of ‘image quality as good as possible’ to ‘image quality as good as needed’.…”
Section: Discussionmentioning
confidence: 99%
“…and high contrast spatial resolution (HCSR) are the most common physical quantities considered by the most of the authors [124][125][126][127][128][129][130][131][132][133][134][135][136][137]. These are directly related to operator selectable parameters (fluoroscopy mode, field of view (FOV), geometric magnification, exposure factors, focus skin distance and collimation).…”
Section: The Problemmentioning
confidence: 99%
“…In general, such phantoms are used for dose and quantitative image quality assessment, as well as for performance testing of the fluoroscopic equipment . The characterization of the overall performance of a fluoroscopy system can be described by estimating a FOM, which combines image and dose indices during implementation of different operating modes [129][130][131][132][133][134][135][136][137]. However, only a few experimental data are available, considering the radiation dose and image quality indices during intraoperative fluoroscopy in spinal surgery [69,106].…”
Section: The Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…In ERCP there are several studies regarding local and national DRLs (Brambilla et Another tool to achieve optimisation in X -ray imaging procedures is the use of appropriate phantoms, which allow an objective evaluation to reach the optimum balance between patient dose and IQ. Such studies have been reported for various IPs, mainly in cardiology (Kordolaimi et al, 2013 Vassileva et al, 2013). In modern radiological systems, the image intensifier has been replaced by flat panel (FP) detector, due to its several advantages such as, high sensitivity, high spatial and contrast resolution, wide dynamic range, orthogonal field of view, distortion free images and relatively insensitivity to magnetic field (Vano et al, 2005).…”
Section: Chapter 1 -Introduction and Layoutmentioning
confidence: 99%